Proximities and convergences between Mathematical Modeling and STEAM - Coelho, José Ricardo Dolenga; Góes, Anderson Roges Teixeira (Educação Matemática Debate, 2020)
Considering the need for differentiated pedagogical practices enabling the association of student’s reality and other areas of knowledge, so that scientific/school concepts/content have greater meaning, this paper presents the approximation between methodologies Mathematical Modeling and STEAM. Such discussion is indispensable, because when researching the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), no studies involving both methodologies were identified. With this, research presents elements associating similarities in the stages/phases indicated by each methodology, which allow the student, mediated by the teacher, to develop mathematical and physical models to solve current problem situations. Based on the theoretical studies carried out, it is possible to consider that the two methodologies have similarities and can be inserted into the process of Mathemathics teaching and learning, allowing the student to be the protagonist in the construction of his knowledge, not only of mathematical concepts, but also in an interdisciplinary approach.